2021
DOI: 10.1371/journal.ppat.1009860
|View full text |Cite
|
Sign up to set email alerts
|

Robust innate immune responses at the placenta during early gestation may limit in utero HIV transmission

Abstract: In 2019, >90% of new HIV infections in infants globally occurred vertically. Studies suggest intrauterine transmission most often occurs in the third trimester; however, there are no mechanistic studies to support these observations. We therefore obtained early/mid-gestation and term placentae from 20 HIV/Hepatitis B/CMV negative women. Isolated primary placental macrophages (Hofbauer cells [HCs]) were exposed to HIV-1BaL and/or interferon (IFN)-α, IFN-β, IFN-λ1, and RIG-I-like receptor (RLR) agonists. qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 111 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…140 However, in vitro studies have found that HBCs limit HIV-1 replication by producing IL-10, sequestering HIV in acidic compartments, and reducing the triggering of pro-inflammatory responses that could be detrimental to pregnancy. 141 Zika virus (ZIKV) is a flavivirus that can be transmitted via blood transfusion, sexual contact, or mosquito bite. ZIKV is known for its ability to surmount intrinsic defense mechanisms of the placenta allowing it to reach 10% of developing fetuses 123 resulting in adverse birth defects such as microcephaly.…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%
“…140 However, in vitro studies have found that HBCs limit HIV-1 replication by producing IL-10, sequestering HIV in acidic compartments, and reducing the triggering of pro-inflammatory responses that could be detrimental to pregnancy. 141 Zika virus (ZIKV) is a flavivirus that can be transmitted via blood transfusion, sexual contact, or mosquito bite. ZIKV is known for its ability to surmount intrinsic defense mechanisms of the placenta allowing it to reach 10% of developing fetuses 123 resulting in adverse birth defects such as microcephaly.…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%
“…HIV can cross the placenta and the virions can either be cellassociated, antibody-associated or free (32,33). The virions can interact directly with the tissue resident immune cells including Hofbauer cells and decidual macrophages which express the HIV receptor CD4 and co-receptors C-C chemokine receptor 5 (CCR5), C-X-C chemokine receptor 4 (CXCR4) and Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-Integrin (DC-SIGN) (32,33). In fact, there is evidence that viral replication may occur locally within the placenta based on phylogenetic studies demonstrating genetic divergence between placental and systemic maternal HIV quasi species (34,35).…”
Section: Hiv Infection At the Maternal Fetal Interfacementioning
confidence: 99%
“…HIV can cross the placenta and the virions can either be cell-associated, antibody-associated or free ( 32 , 33 ). The virions can interact directly with the tissue resident immune cells including Hofbauer cells and decidual macrophages which express the HIV receptor CD4 and co-receptors C-C chemokine receptor 5 (CCR5), C-X-C chemokine receptor 4 (CXCR4) and Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-Integrin (DC-SIGN) ( 32 , 33 ). In fact, there is evidence that viral replication may occur locally within the placenta based on phylogenetic studies demonstrating genetic divergence between placental and systemic maternal HIV quasi species ( 34 , 35 ).…”
Section: Hiv Infection At the Maternal Fetal Interfacementioning
confidence: 99%
See 2 more Smart Citations